The association between frequency of vigorous physical activity and hepatobiliary cancers in the NIH-AARP Diet and Health Study - Behrens, Gundula (2013)
Despite a potential preventive effect of physical activity on hepatobiliary cancer, little information is available on the relation between the two. We studied the association between frequency of vigorous physical activity and hepatobiliary cancer among 507,897 participants of the NIH-AARP Diet and Health Study, aged 50 to 71 years at baseline in 1995/1996. During ten years of follow-up, 628 incident cases of liver cancer and 317 cases of extrahepatic biliary tract cancer were registered. Physical activity levels were assigned according to the frequency of engagement in 20 minutes or more of vigorous physical activity per week: never/rarely (lowest level), less than once per week, 1 to 2 times per week, 3 to 4 times per week, 5 or more times per week (highest level). Using Cox regression, multivariate-adjusted relative risks (RR) comparing the highest with the lowest level of physical activity revealed a statistically significant decreased risk for liver cancer (RR=0.64, 95% confidence interval (CI)=0.49–0.84, p-trend<0.001), particularly hepatocellular carcinoma (RR=0.56, 95% CI=0.41–0.78, p-trend<0.001), independent of body mass index. By comparison, multivariate analyses indicated that physical activity was not statistically significantly associated with extrahepatic bile duct cancer (RR=0.86, 95% CI=0.45–1.65), ampulla of Vater cancer (RR=0.66, 95% CI=0.29–1.48), or gallbladder cancer (RR=0.63, 95% CI=0.33–1.21). These results suggest a potential preventive effect of physical activity on liver cancer but not extrahepatic biliary tract cancer, independent of body mass index.